The Effect Of Compaction Temperature On Marshall Parameters Of AC-WC Asphalt Mixtures With Graphene Additives - Nasution, Naya Fadillah; Maizuar, Maizuar; Akbar, Said Jalalul; Usrina, N; Burhanuddin, Burhanuddin (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2025)
This study aims to determine the effect of compaction temperature variation and graphene addition on Marshall parameters in AC-WC asphalt mixtures. The issues raised are premature damage to asphalt layers due to compaction temperatures that do not meet specifications and the lack of studies on the effect of graphene with compaction temperature variation on AC-WC. The materials used include coarse aggregate, fine aggregate, filler, Portland cement, 60/70 penetration asphalt, and graphene with variations of 0.01%–0.05% by weight of the mixture. The compaction temperatures tested were 110°C, 120°C, 130°C, 140°C, and 150°C. Testing was conducted in accordance with the 2018 Revised II General Specifications for Road Construction using the Marshall method. The results showed that adding 0.01% graphene at a compaction temperature of 140°C produced the best performance with a 19.55% increase in stability, yielding a stability value of 1711.367 kg. Density and MQ increased, while VMA, VIM, and flow decreased due to the addition of graphene, but still met the specification range. The decrease in these values demonstrates that graphene functions effectively in asphalt mixtures, improving porosity and strength compared to standard asphalt. At compaction temperatures of 110°C and 120°C, the VIM values exceeded the maximum limits of 9.67% and 7.05%, respectively. This increase could lead to excessive voids in the asphalt, making graphene a viable solution for asphalt construction.